PROFIL PERTUMBUHAN EKONOMI DAN POTENSI WILAYAH KOTA PALANGKARAYA DI PROVINSI KALIMANTAN TENGAH - Handriyanto Setiadi; Ratna Christianingrum (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2016)
Trade area sector manifestly have important role in fostering and growth of economics in a region. Palangka Raya become one of the priority of Central Kalimantan development of its one program content is development of center industrial area, service area, and trade area. Research of regional potency analysis for the development aims to determine the characteristics of trading activity in Palangka Raya, find the relationship/linkages between Palangka Raya and surrounding areas.